Impacts, challenges and suggestions of the electricity market for hydro-dominated power systems in China - Shen, Jian-jian; Cheng, Chun-tian; Jia, Ze-bin; Zhang, Yang; Lv, Quan; Cai, Hua-xiang; Wang, Bang-can; Xie, Meng-fei (Renewable energy, 2022)
Promoting a hydro-dominated electricity market (HEM) is greatly challenging. This study analyzes impacts and challenges of electricity market on hydro-dominated power system operations. The analysis indicates that the HEM exhibits unique difficulties including spatiotemporal hydraulic coupling of cascaded hydropower plants, runoff uncertainties, nonlinear operation constraints, coordination of multiple time scales, as well as transprovincial and transregional power transmission. Two kinds of suggestions are presented to overcome these difficulties for different market objects. The hydropower enterprises are suggested to improve generation prediction level, reconstruct market-based operation rules, implement multiscale nested operations and bidding, strengthen collaborative bidding of different stakeholders, and analyze market demands and competitors. The goal is to improve their competitiveness. The market operators should make efforts to develop accuracy and efficiency of clearing models and predetermine feasible hydropower bidding intervals to ensure power balance and prevent unreasonable spillage. Moreover, a practical and convenient electricity trading platforms is required. It is implied that there is strong necessity to explore characteristic market theories and application technologies combined with hydropower characteristics and actual dispatching needs. •Promoting a hydro-dominated electricity market (HEM) is challenging for China.•The HEM involves complex hydraulic coupling and nonlinear operation constraints.•The impacts and challenges of electricity market on HPSs are described in detail.•Plants should improve the level of prediction, operation, and bidding in the HEM.•Market operators can make efforts to develop clearing models and trading platforms.